Identification and use of polymorphisms to predict possibility in type II diabetes mellitus family using RAPD method - Miftahul Mushlih (Department of D3 Medical Technology Laboratory STIKes Hutama Abdi Husada Tulungagung, 2020)
Type II diabetes mellitus (T2D) is a genetic disorder that becomes an unsolved problem. This is because T2D can be a disorder caused by lifestyle changes and is inherited from parents. This study aimed to determine the polymorphism that distinguishes between T2D and non T2D patients and the result was predicted to the families that has T2D record. The model in this research was descriptive exploratory and consists of 80 samples (30 samples positive T2D, 30 non DM samples and the others are the member of 5 families). Firstly, the analysis was focused on determining differences in polymorphisms and then the results were applied to the 3 families of T2D using A10 Primer. Difference polymorphism was analyzed using chi-square (cl: 95%). Six bands were obtained from PCR-RAPD which a significantly different band at 997 bp. Analysis of T2D has confirmed that 5 families have a clue band. Based on the analysis this report can be used to screen the possibility of someone to have DM type 2.